Safety Maturity Level Improvement Program At PT XYZ A Mineral (Nickel) Mining Company In Central Sulawesi - Reza, Faisal; Cahyono, Rochim Bakti; Prayoga, Benidiktus Tulung; Arrofiq, Muhammad (Rifa'Institute, 2026)
Introduction: The nickel mining industry has high operational risks, thus requiring a mature safety management system. Objective: This study aims to analyze the Safety Maturity Level (SML) in nickel mineral mining operations at PT XYZ based on the parameters in the Decree of the Director General of Mineral and Coal No. 10.K/MB.01/DJB.T/2023. This evaluation is important to identify standard deviations and formulate a program for continuous improvement of safety culture. Methods: This study uses a qualitative and quantitative research design (mixed methods) by assessing four main indicators: worker participation, unit leader responsibility, accident statistical analysis, and risk control efforts. The research instruments include an assessment rubric according to ESDM regulations, in-depth interviews, field observations, and Focus Group Discussions (FGD). Results and Discussion: PT XYZ achieved a total safety performance score of 0.65 out of 1.00, placing the company at the